2019
DOI: 10.1038/s41598-019-47115-6
|View full text |Cite
|
Sign up to set email alerts
|

Trip Centrality: walking on a temporal multiplex with non-instantaneous link travel time

Abstract: In complex networks, centrality metrics quantify the connectivity of nodes and identify the most important ones in the transmission of signals. In many real world networks, especially in transportation systems, links are dynamic, i.e. their presence depends on time, and travelling between two nodes requires a non-vanishing time. Additionally, many networks are structured on several layers, representing, e.g., different transportation modes or service providers. Temporal generalisations of centrality metrics ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…It was also shown that when these indicators increase the rankings in the scheduled and realised network tend to be more different. This remains true also when the cancelled flights are excluded from the analysis (see supplementary figure S3 of [8]), proving that the effect of missed connection is recognised. Differently from Katz centrality, in Trip centrality the parameter α weighting the use of one link can be chosen without constraints, because all counted walks are made of a finite number of jumps (at most one per time-frame).…”
Section: B Centrality Metricsmentioning
confidence: 66%
See 2 more Smart Citations
“…It was also shown that when these indicators increase the rankings in the scheduled and realised network tend to be more different. This remains true also when the cancelled flights are excluded from the analysis (see supplementary figure S3 of [8]), proving that the effect of missed connection is recognised. Differently from Katz centrality, in Trip centrality the parameter α weighting the use of one link can be chosen without constraints, because all counted walks are made of a finite number of jumps (at most one per time-frame).…”
Section: B Centrality Metricsmentioning
confidence: 66%
“…Differently from Katz centrality, in Trip centrality the parameter α weighting the use of one link can be chosen without constraints, because all counted walks are made of a finite number of jumps (at most one per time-frame). For values of α large enough, say α > 0.05, the ranking according to Trip centrality differs significantly from the ones obtained by Katz or degree centrality (see [8]), as such values of the parameter give importance to walks longer than one, on whose counting Trip Centrality differs.…”
Section: B Centrality Metricsmentioning
confidence: 73%
See 1 more Smart Citation
“…We argue that both the temporal and multiplex structure must be accounted for when computing centrality metrics, as they both have a comparable influence on the flow of information 13 . The temporal structure implies that information (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…minimum connecting time between two flights). These characteristics have rarely been considered in previous works on temporal networks (though see 13 15 ).…”
Section: Introductionmentioning
confidence: 99%